Complexifying Facilitation by Immersing in Lived Experiences of on-the-fly Facilitation. (June 2021) - van Laere, Joeri; Lindblom, Jessica; de Wijse-van Heeswijk, Marieke
Background: Describing the role of a facilitator often results in to-do lists resembling a recipe or a laundry list to follow. Such lists fail to grasp the inherent complexity offacilitation and are not very useful in guiding facilitators when, why and if they should intervene in the unfolding live performance of that day. Aim: To develop a deeper understanding of on-the-flyfacilitation by analyzing rich empirical accounts of in-situfacilitation episodes. Intervention: Sixfacilitation episodes were through purposeful sampling selected from a body of hundreds of interventions in forty-seven performedcrisis management training exercises in Swedish municipalities. Each full-daycrisis management simulation-game had between fifteen and fifty participants involving politicians, administrative managers andcrisis management staff. Method: Anauto-hermeneutical phenomenological analysis of sixlived experiences offacilitation episodes was conducted to understand what the facilitator observed and how afacilitation intervention was applied. Results: On-the-fly-facilitation is instantaneous, but draws simultaneously on awareness of the past, present and future.Facilitation needs are foreseen during design and they influence current attentiveness and coaching. Unfolding game-play needs to be grasped quickly. Potential future consequences of intervening or not intervening are evaluated within a limited window of opportunity. Due to these circumstances, facilitation is multi-skilled, arbitrary and fallible. Suchmuddiness of on-the-flyfacilitation requires courage from the facilitator. Conclusions: In order to better understand howfacilitation skills and roles actually are performed, thefacilitation literature desperately needs a larger number of rich empirical accounts of interesting in-situfacilitation . Elaborate analysis of suchlived experiences could develop understanding as to how available skills, situational circumstances as well as the unfolding interaction between players and facilitators actually develop into a facilitation intervention. This could generate more complex theoretical understanding of how to applyfacilitation skills, in addition to theories that list what skills a facilitator should master.